Development of Canva-Based Learning Media for 11 Grades of SMAN 3 Lamongan on Physics Material - Endah Kurniasih; Ibut Priono Leksono; Ujang Rohman (UNDIKMA, 2023)
Media has a significant meaning in its presence in the learning process. This is because the presence of the media acts as an intermediary in assisting the delivery of complex material. Media can simplify the delivery of material and concretize abstract materials. Canva for Education is an online application for making learning media in schools that are used for ADDIE-oriented learning in Physics class XI SMAN 3 Lamongan, so that students' motivation and learning effectiveness can increase, as well as add a variety of meaningful technology-based learning media. The ADDIE development model is used in this development research. Data collection was carried out using a questionnaire instrument to material experts, learning designs, media, and respondents. The respondent for the peer-to-peer trial was a physics teacher at SMAN 3 Lamongan. Respondents for the individual, small group, and field trials were students of class XI at SMAN 3 Lamongan. The results of due diligence by material experts, learning design, and media were 83%, 96%, and 93%. The results of the analysis of peer, individual, small group, and field trials were 92%, 93%, 88%, and 90%. Based on the results of the validation and trials, Canva for Education's ADDIE-oriented technology-based learning media in Physics subject for class XI SMAN 3 Lamongan is concluded to be very suitable as a media for learning Physics.